CULTURAL TRANSMISSION THROUGH SYMBOLS - Abdukhalimova Sarvinozkhon Usmanali kizi (Western European Studies, 2025)
This article explores the integral role of symbols and communication in human culture as continuous and dynamic processes that shape interpersonal relationships. It defines symbols as multi-faceted tools for expression and understanding, emphasizing their significance in conveying meaning across generations. The article highlights the complexities involved in encoding and decoding messages, where individual perceptions create discrepancies in meaning, leading to differences in communication outcomes. Furthermore, it categorizes interaction patterns into symmetrical and complementary dynamics, illustrating how these structures influence communication behavior. Ultimately, the piece underscores the fluidity of symbols and the inherent imperfection of human communication, both of which are essential for personal development and the evolution of cultural knowledge.
Keywords: symbols; human communication; encoding and decoding; meanings